2013
DOI: 10.1530/joe-13-0263
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of endothelium behavior by progesterone and medroxyprogesterone acetate

Abstract: Medroxyprogesterone acetate (MPA) is a synthetic progestin commonly used in hormone replacement therapy (HRT). The aim of this research was to study and compare the effect of progesterone (Pg) and MPA on the regulation of cellular events associated with vascular homeostasis and disease. Platelet adhesion to endothelial cells (ECs), nitric oxide (NO) production, and cell migration were studied using murine ECs in vitro exposed to the progestins. After 7 min of treatment, MPA significantly inhibited NO synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Progesterone induces repair of epithelial cells in the endometrium and myelin fibers in the central nervous system [ 44 , 45 ]. This repair of myelin fibers by P4 [ 46 ] is one factor mediating how this reproductive hormone mitigates the progression of multiple sclerosis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone induces repair of epithelial cells in the endometrium and myelin fibers in the central nervous system [ 44 , 45 ]. This repair of myelin fibers by P4 [ 46 ] is one factor mediating how this reproductive hormone mitigates the progression of multiple sclerosis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pablo et al found that P4 promotes nitric oxide (NO) synthesis, EC viability and tube formation, whereas MPA exerts an opposite effect. Irreversible NOS inhibitor significantly reduces P4-induced NO production, and blocking PR partially represses both P4- and MPA-mediated actions; the same inhibitory effect was observed after the treatment of MAPK and PI3K inhibitor [ 31 , 83 ], implying NOS and its related signaling pathways are involved in vessel development. It is not unusual for studies to find discrepancy between the biologic effects of P4 and MPA, with Simoncini et al finding P4-mediated PR promotes the production of NO and endothelial NOS via ERK/Akt phosphorylation, while MPA has an opposite effect.…”
Section: Downstream Factors Involved In Progestogen-mediated Neovascularizationmentioning
confidence: 87%
“…Due to the different structures among progestogens, altering molecular biofunctions makes natural P4 and synthetic progestins work in individual patterns. Many papers have revealed drug-specific influences: P4 mainly upregulates VEGF in the basal layers of epithelial cells, while the effect of MPA is primarily exerted on stromal and epithelial cells [ 156 ]; P4 modulates vascular remodeling by inducing VEGF and endothelial NOS, while the regulation of MPA mainly depends on platelet activation [ 31 , 83 ]. Progestins were proved to have a different regulatory intensity for the same angiogenic factor [ 148 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several hormone replacement therapy trials have observed that medroxyprogesterone acetate (MPA) treatment could increase risk of coronary disease and stroke (14,34). Unlike natural progesterone, MPA, as a synthetic progesterone, contains androgen activity (6). In addition, progesterone may act antagonistically to estrogen in menopausal hormone treatments because there exists competition with hormone receptors and other coregulators for binding to essential sites on the promoter (39).…”
Section: Discussionmentioning
confidence: 99%